Analysis of expressed sequence tags (ESTs) from a normalized cDNA library and isolation of EST simple sequence repeats from the invasive cotton mealybug Phenacoccus solenopsis. (21st January 2015) - Li, Hui; Lang, Kun‐Ling; Fu, Hai‐Bin; Shen, Chang‐Peng; Wan, Fang‐Hao; Chu, Dong
Abstract: The cotton mealybug, Phenacoccus solenopsis Tinsley, is a serious and invasive pest. At present, genetic resources for studying P. solenopsis are limited, and this negatively affects genetic research on the organism and, consequently, translational work to improve management of this pest. In the present study, expressed sequence tags (ESTs) were analyzed from a normalized complementary DNA library of P. solenopsis . In addition, EST‐derived microsatellite loci (also known as simple sequence repeats or SSRs) were isolated and characterized. A total of 1107 high‐quality ESTs were acquired from the library. Clustering and assembly analysis resulted in 785 unigenes, which were classified functionally into 23 categories according to the Gene Ontology database. Seven EST‐based SSR markers were developed in this study and are expected to be useful in characterizing how this invasive species was introduced, as well as providing insights into its genetic microevolution.